Durability of high temperature polymer electrolyte membrane fuel cells in daily based start/stop operation mode using reformed gas. (29th June 2015) - Kim, Jintae; Kim, Minjin; Lee, Bong-Gu; Sohn, Young-Jun
Abstract As the best substitute for traditional low-temperature proton exchange membrane (PEM) fuel cells, phosphoric acid-doped polybenzimidazole (PBI)-based high-temperature PEM fuel cells have been studied. However, it has been reported that the performance of PBI fuel cells decreases more rapidly than the performance of low-temperature PEM fuel cells. At first, it was determined the effect of the composition of the gas supplied to the anode on the performance characteristics of high-temperature PEM fuel cells. It was observed that CO2 and CO reduced the cell voltage, while CH4 had an insignificant effect. The second, to investigate the degradation of high-temperature PEM fuel cells according to the composition of the simulated reformate, daily based start-up and shut-down (DSS) tests were carried out at 0.2 A cm−2 and 150 °C. Degradation rates with pure hydrogen, and two kinds of simulated reformate were 170, 160, and 270 μV h−1, respectively. Equivalent circuit (EC) modeling using electrochemical impedance spectroscopy (EIS) was performed to confirm the variations for certain resistances through the DSS tests. Electronic transfer resistance at the anode increased significantly during the DSS tests with reformed gas. Consequently, it was verified that reformed gas that included a small amount of CO did not significantly decrease the durability of high-temperature PEM fuel cells, but the cell voltage diminished when the CO concentration increased.